2017
DOI: 10.4103/ijmm.ijmm_17_144
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Carriage of Carbapenem-Resistant Enterobacteriaceae and Risk Factor Analysis in Hospitalised Patients: A Single Centre Study from India

Abstract: The study is the first from India to show high CRE carriage in patients admitted to a tertiary care centre and emphasises the need of strict antimicrobial stewardship implementation in hospitals to prevent dissemination of multidrug-resistant CRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
7
13
0
Order By: Relevance
“…In this study, pneumonia/chronic pulmonary disease, previous use of fluoroquinolone, and nasogastric tube were documented as risk factors. These results are consistent with previous reports [ 13 , 14 , 15 , 16 , 19 , 20 ]. Pneumonia/chronic pulmonary disease may be associated with CPE colonization or infection in the lung.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, pneumonia/chronic pulmonary disease, previous use of fluoroquinolone, and nasogastric tube were documented as risk factors. These results are consistent with previous reports [ 13 , 14 , 15 , 16 , 19 , 20 ]. Pneumonia/chronic pulmonary disease may be associated with CPE colonization or infection in the lung.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we report a 3.8% prevalence of CPE among patients in an ICU, which is much higher than reports from Kor-GLASS, because the population in the present study comprised of patients admitted in ICU. The prevalence of this study is similar or lower compared to other regional reports: 12% in Israel, 5.4% in the USA, 6.6% in China, 12.2% in Japan, and 18.1% in India [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 81%
“…Screening of rectal swab specimens for CR-GNB carriage at the time of ICU admission may help to identify patients who require isolation or who are at high risk of developing endogenous infections and require frequent monitoring during their ICU stay. CR-GNB colonization among patients admitted to an ICU has previously been studied, and various carriage rates have been reported (10)(11)(12)(13)(14)(15). In the present study, we found that 11.6% and 9.5% of patients admitted to ICUs were colonized with CR-GNB and CP-GNB, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…However, this study re-asserts the central role of intra-and inter-hospital transmission for the most burdensome carbapenemase-positive clones that are already well-established within the human population. Indeed, strong links between hospital care and the acquisition of carbapenem-non-susceptible bacteria have previously been noted [14,[25][26][27][28], and the impact of community [29] or animal and environmental reservoirs [10] on clinical cases remains circumstantial. In this context, we note that a large faecal resistome analysis from slaughter pigs and broilers failed to identify carbapenemase genes in 181 pig and 178 poultry farms from nine European countries [30].…”
Section: Discussionmentioning
confidence: 99%